Kegiatan Peningkatan Kemampuan Numerasi Siswa Sekolah Dasar Melalui Kampus Mengajar - Melinda, Linda Daniati (LPPM POLITEKNIK LP3I, 2024)
The Primary school students' numeracy skills are important competencies that include understanding, analysing and applying mathematical concepts in everyday life. This article discusses the implementation of innovative programmes such as jaritmatika, mathventures, clocktastic, and snakes and ladders numeracy in improving students' numeracy skills. The research used is a classroom action research (PTK). Through an interactive and contextualised approach, the programme successfully increased students' motivation and understanding of basic mathematical concepts. The evaluation showed a significant improvement in students' numeracy assessment results, supported by improved teaching quality and active student engagement. This research emphasises the importance of concept-based learning approaches and innovation to improve the quality of numeracy education in Indonesia.